1995
DOI: 10.1007/bf00027060
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetical studies in wheat XVI. Chromosome location of a new gene for resistance to leaf rust in a Japanese wheat-rye translocation line

Abstract: A leaf rust resistant wheat-rye translocation stock, ST 1, introduced from Japan, comprised distinct morphological types . One type possessed a T1BL . IRS chromosome with genes Lr26, Yr9 and Sr31 . A second type carried a new gene, Lr45, located in a large segment of rye chromosome translocated to wheat chromosome 2A . Its structure was identified as T2AS-2RS .2RL. Despite the homoeology of the 2A and 2R chromosomes and the high level of compensation provided by the translocation, Lr45 was not normally inherit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 17 publications
1
34
1
2
Order By: Relevance
“…As QLr.sfr-1BS proved to be effective in different genetic backgrounds and was mapped very close (less than 1 cM) to Xgwm604, this marker would be suitable for marker assisted selection for leaf rust resistance. Other mapping studies have identified the leaf rust resistance gene Lr26, which was derived from a 1B/ 1R wheat-rye translocation, on chromosome arm 1BS (McIntosh et al 1995a;Mago et al 2002). Furthermore, a major leaf rust resistance QTL located on 1BS was also detected in the CIMMYT spring wheat germplasm (William et al 1997).…”
Section: Discussionmentioning
confidence: 95%
“…As QLr.sfr-1BS proved to be effective in different genetic backgrounds and was mapped very close (less than 1 cM) to Xgwm604, this marker would be suitable for marker assisted selection for leaf rust resistance. Other mapping studies have identified the leaf rust resistance gene Lr26, which was derived from a 1B/ 1R wheat-rye translocation, on chromosome arm 1BS (McIntosh et al 1995a;Mago et al 2002). Furthermore, a major leaf rust resistance QTL located on 1BS was also detected in the CIMMYT spring wheat germplasm (William et al 1997).…”
Section: Discussionmentioning
confidence: 95%
“…C-banding and GISH analyses located the leaf rust resistance gene, designated Lr45, on the wheat-rye translocation chromosome T2AS-2R#3S.2R#3L (Figure 25), which consists of the long arm of 2R, a 1.71 #m long segment of the short arm of 2R, and a distal 2.68 #m long segment of 2AS. Because meiotic pairing analysis, as discussed above, revealed that the rye segment in the Transec translocation, having Lr25, was derived from 2RL it remains to be shown that the leaf rust resistance gene Lr45 in the T2AS-2R#3S.2R#3L translocation line is different from Lr25.The breakpoint is at FL 0.39 (Table 4) (McIntosh et al, 1995a). Although the T2AS-2R#3S.2R#3L translocation is of the compensating type, its male transmission frequency is reduced.…”
Section: Lr25/pm7 (Transec)mentioning
confidence: 99%
“…Important wheat leaf rust resistance genes have been located on specific wheat chromosomes since Sears introduced this mapping method approximately 70 years ago (Sears, 1939). These genes include Lr18 on chromosome 1A (Bai et al, 1998); Lr45 on chromosome 2A (McIntosh et al, 1995); genes resistant to P. triticina, P. graminis, P. striiformis, and Erysiphe graminis on chromosome 2A (Bariana and McIntosh, 1993); 2 inserted chromosomal segments carrying resistance genes to leaf rust and greenbug initially located on chromosome 7S of Triticum speltoides and then transferred to chromosome 7A of hexaploid wheat (Dubcovsky et al, 1998), and Lr39 introgressed from Aegilops tauschii on chromosome 2D (Raupp et al, 2001).…”
Section: Introductionmentioning
confidence: 99%